Conational Drivers, Mainly Advertisement Influencing Brand Preference of Consumer Durable Goods: An Experimental Analysis in North India - Aarti, Chahal (International Journal of Scientific Research and Management (IJSRM), 2013)
Brand preference is understood as a measure of brand loyalty in which a consumer exercises his decision to choose a particular brand in presence of competing brands. Everyday consumers are exposed to thousands of voices and images in magazines, newspapers, and on billboards, websites, radio and television. Every brand attempts to steal at least a fraction of a person‟s time to inform him or her of the amazing and different attributes of the product at hand. This study aims at discussing the cognitive factors that determine brand preference among consumers based on empirical research. Brand attributes including price, quality, features, image which influence consumer perceptions and temporal association with brands are critically examined in the study. Researcher also focuses upon the various types of advertisement and aspects of advertisement. The study makes use of statistical techniques such as percentage, chi square test in analyzing the data for finding the result. The result shows that there is a significant relationship between advertisements and the choice of the brand. The perception of employees differs significantly regarding the conational drivers, type of advertisement and aspects of advertisement. Consequently the recommendations support for the noteworthy of consumer preference which will bring a constructive brand selection.